climatic basis for microrefugia: the influence of terrain on climate - DOBROWSKI, SOLOMON Z (Global change biology, 2011)
There is compelling evidence from glacial and interglacial periods of the Quaternary of the utilization of microrefugia. Microrefugia are sites that support locally favorable climates amidst unfavorable regional climates, which allow populations of species to persist outside of their main distributions. Knowledge of the location of microrefugia has important implications for climate change research as it will influence our understanding of the spatial distribution of species through time, their patterns of genetic diversity, and potential dispersal rates in response to climate shifts. Indeed, the implications of microrefugia are profound and yet we know surprisingly little about their climatic basis; what climatic processes can support their subsistence, where they may occur, their climatic traits, and the relevance of these locations for climate change research. Here I examine the climatic basis for microrefugia and assert that the interaction between regional advective influences and local terrain influences will define the distribution and nature of microrefugia. I review the climatic processes that can support their subsistence and from this climatic basis: (1) infer traits of the spatial distribution of microrefugia and how this may change through time; (2) review assertions about their landscape position and what it can tell us about regional climates; and (3) demonstrate an approach to forecasting where microrefugia may occur in the future. This synthesis highlights the importance of landscape physiography in shaping the adaptive response of biota to climate change.